Autopsy of a metaphor: the origins, use and blind spots of the ‘infodemic’ - Simon, FM; Camargo, CQ (SAGE Publications, 2021)
In 2020, the term ‘infodemic’ rose from relative obscurity to becoming a popular catch-all metaphor, representing the perils of fast, wide-spreading (false) information about the coronavirus pandemic. It featured in thousands of academic publications and received widespread attention from policymakers and the media. In this article, we trace the origins and use of the ‘infodemic’ metaphor and examine the blind spots inherent in this seemingly intuitive term. Drawing from literature in the cognitive sciences and communication studies, we show why information does not spread like a virus and point out how the ‘infodemic’ metaphor can be misleading, as it conflates multiple forms of social behaviour, oversimplifies a complex situation and helps constitute a phenomenon for which concrete evidence remains patchy. We point out the existing tension between the usefulness of the widespread use of the term ‘infodemic’ and its uncritical adoption, which we argue can do more harm than good, potentially diluting the quality of academic work, public discourse and contributing to state overreach in policymaking.